ANALISIS KEPUASAN PETANI TERHADAP KINERJA PENYELENGGARAAN PENYULUHAN PERTANIAN DI KABUPATEN ENDE PROVINSI NUSA TENGGARA TIMUR - Reyna Virginia Nona; Ida Ayu Komang Juniasih (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2020)
ABSTRACT Analysis of Farmer Satisfaction on Performance Organization of Agriculture Instructor in Ende District of East Nusa Tenggara Province. This study aims to analyze farmers' satisfaction with the performance of agricultural instructor services in Ende District based on the expectations and reality experienced by farmers. This study used 125 farmers as samples. Determination of the sample is done by purposive sampling, where the area sampling technique is used to determine the sample area. Farmer samples are taken randomly using the random number approach in the excel program. This study found that the instructor's ability to utilize the results of research; commitment of extension workers in fulfilling promises; the accuracy of the technology and information media; completeness of technology and information media; the ability of extension agents in using technology and information media, are very important factors in increasing farmer satisfaction with the performance of agricultural extension services in Ende District. This study found that in the preparation of guidelines for instructor services it is also necessary to pay attention to aspects of the characteristics of the region because it will affect the response of farmers to the implementation of agricultural extension.Keywords: satisfaction, performance, farmers, agriculture instructor ABSTRAK Penelitian ini bertujuan untuk menganalisis kepuasan petani terhadap kinerja penyelenggaraan penyuluhan pertanian di Kabupaten Ende berdasarkan harapan dan kenyataan yang dialami petani. Penelitian ini menggunakan 125 orang petani sebagai sampel. Penentuan sampel tersebut dilakukan secara purposive sampling, dimana teknik area sampling digunakan untuk penentuan wilayah sampel. Sampel petani diambil secara acak dengan menggunakan pendekatan angka random pada program excel. Penelitian ini menemukan bahwa faktor kemampuan penyuluh memanfaatkan hasil riset; komitmen penyuluh dalam memenuhi janji; ketepatan media teknologi dan informasi; kelengkapan media teknologi dan informasi; kemampuan penyuluh dalam menggunakan media teknologi dan informasi, merupakan faktor-faktor yang sangat penting dalam meningkatkan kepuasan petani terhadap kinerja penyelenggaraan penyuluhan pertanian di Kabupaten Ende. Penelitian ini menemukan bahwa dalam penyusunan pedoman penyelenggaraan penyuluhan perlu juga memperhatikan aspek karakteristik wilayah karena akan mempengaruhi respon petani terhadap penyelenggaraan penyuluhan pertanian.  Kata kunci: kepuasan, kinerja, petani, penyuluh pertanian